Generation of a mutant population for TILLING common bean genotype BAT 93 - Porch, Timothy G.; Blair, Matthew W.; Lariguet, P; Galeano Mendoza, CH (2009)
Common bean (Phaseolus vulgaris) is the major food legume worldwide, making it an important target for novel approaches of genetic analysis. This study evaluated the use of ethyl methane sulfonate (EMS) for the generation of a mutant population for targeted induced local lesions in genomes (TILLING) in common bean. TILLING is a powerful reverse genetics approach that uses a large mutant population for identi?cation of mutants in loci of interest. Based on overall survival, development, and yield of treated seed, 40 mM EMS was found to be an appropriate concentration for the generation of a mutant population in common bean genotype BAT 93. Higher concentrations of EMS resulted in survival rates of less than 10% and lower concentrations resulted in the generation of fewer mutants. Based on TILLING results from other species, a population of 5000 lines is estimated to be suf?cient for saturation of the common bean genome. Phenotypic mutation frequencies and the isolation of targeted mutations in the BAT 93 mutant population indicate that mutagenesis was effective.